The End of Multi-Fibre Arrangement and Firm Performance in the Textile Industry: New Evidence (The Pakistan Development Review, 2013)
Using a sample of 321 textile and clothing companies for the years 1992 to 2010, this paper analyses the effect of quota phase-outs on firm-level efficiency in Pakistan following the end of the Multi-Fibre Arrangement (MFA). It highlights sectoral heterogeneity within the manufacturing industry as a result of MFA expiration. The empirical methodology uses the structural techniques proposed by Olley and Pakes (1996), and Levinsohn and Petrin (2003) in order to take care of endogeneity in the estimation of production functions. The results differ for the two industries: MFA expiration lead to an increase in the average productivity of textile producing firms but a significant reduction in the mean productivity of clothing producers. We offer a number of explanations for this outcome, such as a change in the input and product mix, entry by non-exporters in the clothing sector, and sectoral differences in quality ladders. A number of crucial policy lessons can be drawn from the findings of this study. JEL Classification:F13; F14; D24; C14; O19 Keywords: Multi-Fibre Arrangement, Trade Liberalisation, Productivity, Firm Heterogeneity, Simultaneity and Production Functions, Endogeneity of Protection